2017
DOI: 10.1186/s40490-017-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Variability in seed germination and seedling growth at the intra- and inter-provenance levels of Nothofagus glauca (Lophozonia glauca), an endemic species of Central Chile

Abstract: Background: Patterns of seed germination and subsequent seedling growth of the endemic species Nothofagus glauca (Phil.) Krasser (Lophozonia glauca) (Hualo) were studied in two provenances from Mediterranean Central Chile (pre-Andean mountain range provenance and coastal range provenance). The main aim of the study was to determine differences in seed germination and seedling growth at the intra-and inter-provenance levels. Methods: The experiment was carried out with seeds from two provenances and four to fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
8
0
3
Order By: Relevance
“…The mentioned authors [33] revealed that the Mediterranean population Buje exhibits clear genetic differentiation from other Croatian coastal populations. A similar effect of genetic variability on seedling growth was noted for several other species [34][35][36][37]. In this research, we found no evidence of a decisive influence of seed weight on germination performance, with only extremely low correlations being observed between these two parameters (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…The mentioned authors [33] revealed that the Mediterranean population Buje exhibits clear genetic differentiation from other Croatian coastal populations. A similar effect of genetic variability on seedling growth was noted for several other species [34][35][36][37]. In this research, we found no evidence of a decisive influence of seed weight on germination performance, with only extremely low correlations being observed between these two parameters (Table 3).…”
Section: Resultssupporting
confidence: 87%
“…The reported germination percentages differ but this may be explained by differences in season of collection, the mast seeding habit of the species, and the geographical origin of seeds. Santelices et al (2017) (Pérez-Fernández and Gómez-Gutiérrez 2007). For those species with seeds that show dormancy, it is advisable to develop effective strategies to ensure a greater and more homogenous percentage of germination and uniform seedling development.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapopulation variability in germination is common as a result of genetic factors and climate variability during seed ripening (Baskin and Baskin 1973). Strong regional variability in seed germination was found in Nothofagus glauca when contrasting 9 populations from two differentiated regions in Chile revealing higher variability within regions than between them (Santelices Moya et al 2017). Germination variability together with high intraspecific variability in persistence traits may maximize plant long-term fitness through a bed-hedging strategy, ensuring regeneration at different time scales (Tielbörger et al 2011;Huang et al 2016).…”
Section: Variability In Seed Traits In Geographically Near Populationsmentioning
confidence: 99%